Word Formation Processes and Meanings in English-Based K-Pop Group Names - Nurhidayah, Dinda Tri; Wulandari, Novitri; Tyas, Dinda Ayuning; Aziz, Dzaki Naufal (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This paper analyzes the formation and meaning of English-based K-pop group names through morphological and semantic approaches. As K-pop has become a global phenomenon, it is undeniable that English plays a significant role in shaping its international identity and image. Therefore, this study attempts to identify the types of word formation processes used in English K-pop group names and describe their meanings. This study applies Yule's (2020) theory of word formation, which consists of compounding, blending, clipping, acronyms, and other processes, as well as Leech's (1981) theory of meaning. Thirty K-pop group names were collected from official and valid online sources and analyzed qualitatively. The results show that the most dominant process is compounding, followed by acronyms and blending. These processes are commonly used because they make group names shorter, more creative, and more memorable. Semantically, the most frequently found meaning is connotative meaning. This reflects how K-pop names contain emotions, identity, and creativity beyond their literal or direct meanings. In general, this study shows that K-pop group names do not happen by chance; instead, they have been carefully designed to reflect symbolism and branding. Therefore, this study highlights that linguistic creativity through morphology and semantics is an important factor in shaping how language can create meaning, bind cultures, and play a vital role in global entertainment.